2006
DOI: 10.1021/op060170h
|View full text |Cite
|
Sign up to set email alerts
|

Perspective on Solvent Use in the Pharmaceutical Industry

Abstract: Solvent use consistently accounts for between 80 and 90% of mass utilization in a typical pharmaceutical/fine chemicals (nonpolymer) batch chemical operation. Moreover, within these operations, solvents play a dominant role in the overall toxicity profile of any given process; i.e. on a mass basis, solvents account for the largest proportion of chemicals of concern used in the process. However, for the typical synthetic organic chemist, solvents are just a medium in which a reaction takes place; the interest i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
454
0
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 623 publications
(464 citation statements)
references
References 18 publications
4
454
0
6
Order By: Relevance
“…From a careful assessment of many of the synthetic routes to chemical products, solvents have been found to be one of the biggest mass contributors [45], as the use of solvents can lead to higher yields and thus, an improved environmental performance. This is particularly the case in the fine chemicals and pharmaceutical sectors, where the solvents typically contribute 80% to 90% of the mass intensity of a process [46].…”
Section: Si and Wimentioning
confidence: 99%
“…From a careful assessment of many of the synthetic routes to chemical products, solvents have been found to be one of the biggest mass contributors [45], as the use of solvents can lead to higher yields and thus, an improved environmental performance. This is particularly the case in the fine chemicals and pharmaceutical sectors, where the solvents typically contribute 80% to 90% of the mass intensity of a process [46].…”
Section: Si and Wimentioning
confidence: 99%
“…Constable et al [6] have previously reported that 80-90 % of the waste mass generated by typical batch chemical operations will often come from the solvent. More recently, estimates from the American Chemical Society Green Chemistry Institute Pharmaceutical Roundtable (ACS-GCIPR) have shown 56 % of the mass needed to produce 1 kg of an active pharmaceutical ingredient (API) will come from solvent [7].…”
Section: Introductionmentioning
confidence: 99%
“…16 Considerando todos os aspectos das transformações químicas sustentáveis, tais como economia de átomos, catálise e eficiência energética, entre outros, o meio reacional tem papel muito importante. De acordo com Constable et al, 17 o solvente da reação representa até 80% do total de toda a massa de materiais para os processos químicos de produção de Ingredientes Farmacêuticos Ativos (Active Pharmaceutical Ingredient, API). Diante disso, grandes indústrias farmacêuticas como a Pfizer, 18 a GSK, 19 e a Sanofi 20 desenvolveram recentemente guias de seleção de solventes para processos químicos aplicados à síntese de APIs.…”
Section: Introductionunclassified